Computer simulation of material behaviour at the notch tip: effect of microrotations on elastic energy release - Moiseenko D. D.; Panin S. V. Sergey Viktorovich; Maksimov P. V.; Panin V. E. Viktor Evgenyevich; Berto F. (Основные принципы и методология физической мезомеханики материалов с иерархической структурой, 2016)
Заглавие с экрана